ANALISIS STRUKTUR DAN SOSIOLOGIS DRAMA MULIH KARYA I NYOMAN MANDA - Kartika Dewi, Ni Putu Harum (Humanis; Volume 15. No.1. April 2016)
This study examines a modern Balinese drama by I Nyoman Manda entitled Mulih in terms of structure and sociological. This topic was chosen in order to understand more about the structure of drama and social problems inherent in the drama Mulih. The theoretical framework used to solve both these problems consists of the theory of the structure anda sociological approaches. This study is divided into four stages, namely: (1) the stage of data collection by using the reading method, (2) in the data procesing stage, the data were analyzed with descriptive analytic method combined with formal methods, (3) the stage of presentation of the results of data analysis using informal methods, (4) the stage of recording and translation techniques. The study found that the elements which build the drama Mulih are a dialog element (situation of dialogic language, dialogue and background, dialogue and action, dialogue and atmosphere, dialogue and character dialogue, a dialogue that reveals a theme or ideasof the story), plot, character and personality, as well as text and space. In addition, this study also revealed social problems which include:poverty, alcoholism, and crime (murder).
Keywords: drama, structure, social problems